HUBUNGAN LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS JATISAMPURNA KOTA BEKASI - Putri Setyo Wulandari; Suhartono Suhartono; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Pneumonia is a major killer of under-five children in the world more than any other disease. In 2014, 206.133 cases of pneumonia in under-five children found in West Java. In 2015, detection rate of pneumonia in Bekasi City is 5.296 cases. This study aimed to analyze the physical environmental of house factors associated with pneumonia in under-five children in working area of Jatisampurna Public Health Center Bekasi City. This study was a case control study with retrospective method. Respondents in the case group were 38 under-five children and of the control group were 38 under-five children. Analyzed using univariate and bivariate with Chi Square and the magnitude of the risks identified by Odds Ratio. The results show from 9 variables studied are four variables related, namely ventilation (p value = 0,011 OR = 3.85), residential density (p value = 0.005 OR = 4.4), lighting (p value = 0, 01 OR = 3.7), and the presence of smokers (p value = 0.02 OR = 3.3). The conclusion from this study is there is a relationship between ventilation, residential density, lighting, and the presence of smokers with the incidence of pneumonia in under-five children in Jatisampurna Public Health Center Bekasi City. The suggestions in this study to people who are his physical environmental of house conditions are still not qualified can do renovations in order to qualify a healthy home.